X-Ray Imaging of Immiscible Fluid Fingering Patterns in a Natural High Porosity Rock - Couture, Cyrille; Papazoglou, Athanasios; Tengattini, Alessandro; Bésuelle, Pierre; Viggiani, Gioacchino (Frontiers in Physics, 2022)
This paper presents the development of a laboratory scale apparatus and first experimental results on the characterization of fingering patterns of immiscible fluids in a porous rock (Fontainebleau sandstone), using three dimensional full-field measurements from x-ray tomography. The few existing studies that have extended experimental investigation of immiscible fluid flow from 2D to 3D have been primarily interested in the pore scale or performed on idealized porous media. While the heterogeneities inherent to natural rocks are known to play an important role on subsurface fluid flow regimes, a limited number of studies have approached the problem of characterizing the time resolved 3D multiphase flow in these material, at the mesoscale. The series of experiments reported in this paper has been performed at a low viscosity ratio, water invasion into oil as the defending fluid, and different capillary numbers (1.8 orders of magnitude). The results illustrate the qualitative transition in the flow regime, from capillary fingering to viscous fingering. While a full quantitative characterization the geometrical features of the fingers will require further technical refinements, a qualitative understanding can be already gathered from the results presented herein.